Novel Nematic all-trans-Perhydrochrysenes - Peter Gschwinder; Hermann Minas; Wolfgang Sucrow (CHIMIA)
The fifteen all-trans-perhydrochrysenes 1ab-1cf were prepared on a stereoselective route and their nematic phases recorded.